1998
DOI: 10.1161/01.cir.98.13.1261
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Relaxation of Collateral Microvessels After Intramuscular Gene Transfer of Vascular Endothelial Growth Factor in a Rat Model of Hindlimb Ischemia

Abstract: Background —Recent investigations have demonstrated the ability of vascular endothelial growth factor (VEGF) to augment the development of collateral arteries in vivo. In vitro studies have suggested that the use of VEGF also improves the endothelium-dependent relaxation of collaterals at the microvascular level. The purpose of this study was to determine in vivo the extent to which vasomotor responses of collateral microvessels are altered after VEGF treatment. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 13 publications
1
58
1
3
Order By: Relevance
“…11 and as a potential treatment for ischemic heart disease. [12][13][14] VEGF-A causes vasodilatation and an increase in blood flow in diverse animal blood vessels and vascular beds, 15,16 effects mediated partly through its ability to stimulate endothelial production of nitric oxide (NO) and prostacyclin. [17][18][19][20] The fall in utero-placental resistance in normal pregnancy is mediated by interstitial extravillous trophoblast secretion of angiogenic and vasodilator signals such as VEGF, to promote local blood flow to the uterus.…”
mentioning
confidence: 99%
“…11 and as a potential treatment for ischemic heart disease. [12][13][14] VEGF-A causes vasodilatation and an increase in blood flow in diverse animal blood vessels and vascular beds, 15,16 effects mediated partly through its ability to stimulate endothelial production of nitric oxide (NO) and prostacyclin. [17][18][19][20] The fall in utero-placental resistance in normal pregnancy is mediated by interstitial extravillous trophoblast secretion of angiogenic and vasodilator signals such as VEGF, to promote local blood flow to the uterus.…”
mentioning
confidence: 99%
“…7 VEGF gene or protein therapy may prove therapeutically useful in local perivascular applications by stimulating vascular protective endothelial functions. 8 VEGF vasodilates and increases blood flow in diverse vascular beds, 9,10 the effects mediated partly through its stimulation of endothelial production of nitric oxide 11 and prostacyclin. 12 The fall in uteroplacental resistance in normal pregnancy is mediated by interstitial extravillous trophoblast secretion of angiogenic and vasodilatory factors such as VEGF, to promote local blood flow to the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that gene transfer of VEGF expression plasmids induced neovascularization and brought significant increased blood flow with restored vasomotion in collateral vessels (Bauters et al, 1994;Asahara et al, 1996) as well as at the microvascular level (Takeshita et al, 1998). However, it remains unclear whether the administration of VEGF alone is adequate to promote the formation of mature vessels that are lined with pericytes or vascular smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%